Pengembangan Potensi Kelor Di Desa Kemuning Lor, Jember - Alfiansyah, Gamasiano; Swari, Selvia Juwita; Pratama, Mudafiq Riyan; Kartika, Ria Chandra; Sasmita, Irene Ratri Andia (Puslitbang Sinergis Asa Professional, 2024)
The goal of the Sustainable Development Goals (SDGs) is to end malnutrition by 2030. Kemuning Lor is a village that produces abundant moringa, but it has not been optimized, especially in tackling stunting. The aim of this activity was to increase the knowledge and skills of the Kemuning Lor village community in processing moringa into moringa modisco that has economic value and can reduce the prevalence of stunting. The methods used include socialization, training and mentoring. The result of this activity was that the community was able to process moringa into products that were healthy and had economic value. We expect that this knowledge and skills can become a strategy in overcoming stunting and improving the economy.